THE EFFECT OF TEACHING TECHNIQUE AND SELF-CONFIDENCE TOWARD STUDENTS’ SPEAKING SKILL - Mahardhika (IJLECR (International Journal of Language Education and Cultural Review), 2019)
The aim of the research was to find out the effect of teaching technique toward students’ speaking skill by controlling their level of self-confidence. The method of the research was an experimental method with 2 x 2 factorial design. The population was deck officers class IV consisting 210 students. The sample was class IV B as experiment class and class IV D as control class. The data was collected by using test and questionnaire. From the result of the study, it is concluded that (1) Students taught by using role play technique get higher scores in speaking skill than taught by using interview technique (Fhitung (5,039) > Ftabel (0,05;1:40) (4,08)), (2) There is an interaction between teaching technique and self-confidence toward speaking skill (Fhitung ( 43,62) > Ftabel (0,05; 1:40) ( 4,08)), (3) There is a significant difference of speaking skill possessed by students whose high self-confidence taught by using role play or interview technique (Qhitung (8,83) >  Qtabel (0,05;4:11) (4,26)), (4) There is a significant difference of speaking skill possessed by students whose low self-confidence taught by using role play or interview technique (Qhitung (4,35) > Qtabel (0,05;4:11) (4,26)). Keywords: speaking skill; teaching technique; self-confidence